2021
DOI: 10.1097/jsm.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Concussion Burden, Recovery, and Risk Factors in Elite Youth Ice Hockey Players

Abstract: Acknowledgements: This research would not have been possible without the support of Hockey Calgary, Hockey Alberta, Hockey Quebec, Hockey Canada, team therapists, team designates, coaches, players and parents. Conflicts of Interest and Source of Funding:No conflicts of interest are declared. We acknowledge the support of Max Bell

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 22 publications
1
24
0
Order By: Relevance
“…Consistent with this, 20% of elite youth ice hockey players were not cleared at 30 days after injury. 22 Zemek et al 23 reported that 30% of children and adolescents (age range, 5-17 years) reporting to the emergency department had persistent symptoms for >28 days. Kontos et al 14 reported that 61% of patients (age range, 12-22 years) assessed at a sports medicine clinic had not yet recovered at 30 days.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consistent with this, 20% of elite youth ice hockey players were not cleared at 30 days after injury. 22 Zemek et al 23 reported that 30% of children and adolescents (age range, 5-17 years) reporting to the emergency department had persistent symptoms for >28 days. Kontos et al 14 reported that 61% of patients (age range, 12-22 years) assessed at a sports medicine clinic had not yet recovered at 30 days.…”
Section: Discussionmentioning
confidence: 99%
“… 10 In youth, 60% of concussions are sustained in sports, and >30% of concussions are expected to be recurrent. 2 , 20 , 22 In youth ice hockey (age range, 11-17 years), concussion rates are high, ranging from 2.8 to 4.2 concussions per 1000 game-hours in leagues allowing body checking and 1.1 to 2.31 concussions per 1000 game-hours in leagues not allowing body checking. 4 , 8 , 9 , 11 Studies evaluating time to clinical recovery in children and adolescents have reported that 15% to 30% remain symptomatic >1 month and 11% remain symptomatic for >3 months.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The primary research objectives for both original cohort studies were different from that of the current study on mouthguard use and concussion risk27–29 However, the data from both cohorts provided an opportunity to examine the issue of concussion and mouthguard use as the data on mouthguard use were available, consistently collected and the timing was fortuitous in light of the policy climate. As such, there was no a priori sample size calculation.…”
Section: Methodsmentioning
confidence: 98%